Relationships between land use and stream chemistry in the Mulberry River basin, Arkansas. (11th May 2022) - Burgess‐Conforti, Jason R.; Moore, Philip A.; Owens, Phillip R.; Miller, David M.; Ashworth, Amanda J.; Hays, Phillip D.; Evans‐White, Michelle A.; Anderson, Kelsey R.
Abstract: The Mulberry River in Arkansas is one of America's National Wild and Scenic Rivers and has been listed as impaired for low pH since 2008. Stream chemistry is directly related to land use and changes in land use can result in degradation of surface waters. Growth of conifers, through afforestation or conversion of native hardwood stands, has been attributed to basin acidification in several regions and may be contributing acid to the Mulberry River basin. The objective of this study was to examine the relationship between land use (i.e., coniferous forest, deciduous forest, mixed forest, and pasture) and stream chemistry of 11 tributaries of the Mulberry River over a 2‐year period. Coniferous forest land use was not correlated with stream pH, neither was stream pH predicted by coniferous forest land use. Acid neutralizing capacity (ANC) was negatively correlated with, and partially predicted by coniferous land use. Total organic carbon was negatively correlated with coniferous land use and positively correlated with deciduous land use. Deciduous land use was positively correlated with SO4 and negatively correlated with total N and NO3 . Spearman's rank correlation and principal component analysis identified significant inverse relationships between stream pH and NO3 and between ANC and NO3, which may suggest that HNO3 may be the primary source of acidity within the Mulberry River basin. Although no relationships were observed between coniferous land use and pH, conifer growth may be affecting the stream buffering capacity of the basin which would increase the susceptibility of the river to acidification.